Relevance of Intangible Asset, Equity Book, and Earning Value on Stock Price in Information Technology Era - Filosofi Putri Aulia; Poppy Sofia Koeswayo; Djoemarma Bede (Universitas Padjadjaran, 2020)
This study aims to provide an overview for issuers related to investors' behavior in using the values presented in financial statements in the information technology era, by measuring the moderation effect of intangible assets on the relevance of earnings and book value of equity on stock prices. It tested using a price multiple moderated regression model and LQ45 indexed issuers on the Indonesia Stock Exchange from 2012 to 2018 as a sample. The results of the study show that investors in the Indonesian capital market use the magnitude of profits and intangible assets as a material for consideration in making investment decisions, and no longer use book value of issuer's equity. They do not fully switch to using intangible assets as the creator of the main value of issuers but instead use them as one of the considerations in buying shares of an issuer. However, now investors use the value of intangible assets more dominant than using the value of profits.